Pengetahuan Apoteker terkait Covid-19 selama Pandemi - Fatiha, Chilmia Nurul; Rahmadani, Azmi; Widyaningrum, Naniek (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2025)
Pharmacists’ role during Covid-19 pandemic is important in order to prevent and reduce the transmission rate. Pharmacist need to have good level of knowledge to ensure the role. This study aims to determine the level of pharmacists’ knowledge regarding Covid-19 and related factors. This is an observational study with cross-sectional approach. A questionnaire regarding Covid-19 was distributed to webinar participants in December 2021. The questionnaire is consisted of demographic questions and 15 Covid-19 knowledge questions. A total of 333 pharmacists responded, consisting of 32.4% community pharmacists, 33.9% hospital pharmacists, 24.0% clinical pharmacists, and 9.6% public health center pharmacists. Pharmacists have good knowledge of the causative virus (92%), symptoms (95.3%), supporting examinations (90.2%), therapy (95.8%), and prevention of Covid-19 transmission (94.4%) . Pharmacists' knowledge that needs to be improved is regarding vaccine storage (69.4%) and antibiotic use (56.1%). Semarang City pharmacists have good knowledge about Covid-19. Pharmacist knowledge was related to workplace (p<0.001) and length of work (p<0.001).